Pemikiran Pendidikan Ibn Tufail: Studi Atas Kitab Hay Ibn Yaqzan - Lis safitri; Nurlaela Nurlaela; Ulul Huda; Kuntarto Kuntarto; Muhammad Riza Chamadi (Matan : Journal of Islam and Muslim Society, 2019)
Abu Bakr ibn Tufail, known as great Islamic philosopher, meanwhile his education idea can be found in Hayy ibn Yaqzan, his magnum opus. He lived at the golden age of Andalusia in middle age, but his education idea appropriates as a contemporary teaching model. This paper has been written by analyzing and comparing Hayy ibn Yaqzan with contemporary teaching models. Ibn Tufail used rationality and intuition as a major source of human knowledge, both represent equal knowledge. His teaching model has the same characteristics as personal method teaching with a scientific approach. He hammered at the development of self creativity of problem-solving. Discovery method and inquiry methods used as his teaching method with neuro language program of metaphor and analyze case study as a technique of learning.